Norovirus in Pediatric Gastroenteritis: A Study in Argentine Hospitals Before and After the Introduction of Universal Rotavirus Vaccination - Gomes, Karina A.; Rivero, Karina A.; Barrios Mathieur, Christian; Degiuseppe, Juan I.; Cortes, Paulo R.; Gonzalez, Patricia A.; Zurschmitten, Abel; Castro, María P.; Parreño, Gladys Viviana; Mozgovoj, Marina Valeria; Stupka, Juan A. (MDPI, 2025)
Norovirus (NoV) is a leading cause of acute gastroenteritis (AGE) in young children worldwide. Following the introduction of universal rotavirus (RVA) vaccination in Argentina in 2015, the role of NoV in pediatric AGE warrants evaluation. This study aimed to assess the prevalence, clinical characteristics, and molecular diversity of NoV in children under five years of age, comparing the periods before and after RVA vaccine implementation. Methods: A descriptive observational study was conducted in two pediatric hospitals in Argentina. Stool samples were obtained from both outpatient and hospitalized children presenting with acute gastroenteritis (AGE) during two distinct one-year periods: 285 samples from the pre-vaccination period (2011–2012) and 212 samples from the post-vaccination period (2019–2020). NoV, RVA and other viral enteropathogens were detected by RT-qPCR or immunoassay. Positive NoV samples were genotyped by Sanger sequencing of the ORF1/ORF2 junction. Results: NoV was detected in 30.1% (86/285) and 23.5% (50/212) of cases in the pre- and post-vaccination periods, respectively. Children under two years of age and inpatients had significantly higher NoV detection in both periods. NoV mono-infections were more frequent in post-vaccination period (72% vs. 50%). NoV GII predominated in both periods, with increased genotype diversity observed post-vaccination, including GII.3[P12], GII.4 Sydney[P16], GII.6[P7], and GII.2[P16]. Conclusions: NoV remains a major cause of pediatric AGE in Argentina, particularly in children under two years old. Although NoV prevalence did not increase after RVA vaccine introduction, its clinical relevance persists. Continued molecular surveillance is essential to monitor genotype dynamics and implement prevention strategies.